Satellite pinpoints ammonia sources globally. (6th December 2018) - Sutton, Mark A.; Howard, Clare M.
Ammonia emissions harm humans and the environment. An analysis shows that satellites can locate sources precisely, and could thus help to monitor compliance with international agreements to limit such emissions. High-precision maps of ammonia emissions derived from satellite data.